Saudi EFL English Majors Speech Comprehension and Production: Does Explicit Instruction in Connected Speech Features Make A Difference - Hamouda, Arafat (جامعة أسيوط - كلية التربية, 2017)
Although connected speech is essential for listening comprehension and successful communication, it is rarely treated with proper attention and a few studies have been conducted on how best to teach it in the field of second and foreign language learning. Thus, the present study addresses this gap by examining the effect of explicit instruction in connected speech features on improving overall listening comprehension of the Saudi EFL learners, increasing their “reduced forms” understanding as well as enabling them to produce and use them in daily speech. The study also attempted to explore the EFL students’ perceptions towards instruction of connected speech features. To this end, a group of 56 Saudi English majors studying at Qassim University were asked to participate in the current study. To homogenize the participants’ level of proficiency, the Oxford Placement Test was administered to 56 English majors. Having taken the Oxford Placement Test, forty eight students with the intermediate level of proficiency were selected, and the other eight students were discarded due to their extreme scores. The participants were randomly assigned to two experimental and control groups, each comprising 24 participants. The experimental group received an explicit instruction in connected speech features, while the control group followed the regular instruction designed by the English Department Program A pretest and posttest design was implemented to answer the research questions of the study. Data sources included three tests and questionnaire. The three tests were conducted before and after the treatment, whereas the Questionnaire is only conducted to the experimental group at the end of the treatment. The participants’ scores on the pre-posttests were compared via the paired samples t tests and independent samples t-tests. The quantitative findings confirmed that the experimental group’s mean scores on the posttests were significantly higher than those of the control group. It was thus concluded that teaching connected speech features (i.e. elision, assimilation, and contraction) to Saudi EFL learners could positively affect their speech comprehension and production. In addition, the questionnaire findings demonstrated that the majority of the experimental group had positive perceptions towards the connected speech instruction. Finally, the findings of the study hold a number of pedagogical implications for EFL learners, language teachers, material developers, and those interested in researching connected speech.
Keywords: تعلم اللغة الإنجليزية -- اللغة الإنجليزية